Factors associated with self-reported avoidance of harm reduction services during the COVID-19 pandemic by people who use drugs in five cities in the United States and Canada. (1st December 2022) - Feder, Kenneth A.; Choi, JinCheol; Schluth, Catherine G.; Hayashi, Kanna; DeBeck, Kora; Milloy, Michael-John; Kirk, Gregory D.; Mehta, Shruti H.; Kipke, Michele; Moore, Richard D.; Baum, Marianna K.; Shoptaw, Steven; et al.
Abstract: Background: This study examines individual-level factors associated with avoiding two important health services for people who use drugs—medications for treatment of opioid use disorder and syringe service programs—during the first year of the COVID-19 pandemic. Methods: Data come from two subsamples of people who use drugs who were active participants in one of nine cohort studies in Vancouver, British Columbia; Baltimore, Maryland; Los Angeles, California; Chicago, Illinois; and Miami, Florida. Participants were interviewed remotely about COVID-19-associated disruptions to healthcare. We estimated the association of demographic, social, and health factors with each outcome using logistic regression among 702 participants (medication analysis) and 304 participants (syringe service analysis.) Analyses were repeated, stratified by city of residence, to examine geographic variation in risk. Results: There were large differences between cities in the prevalence of avoiding picking up medications for opioid use disorder, with almost no avoidance in Vancouver (3%) and nearly universal avoidance in Los Angeles, Chicago, and Miami (>90%). After accounting for between-city differences, no individual factors were associated with avoiding picking up medications. The only factor significantly associated with avoiding syringe service programs was higher levels of self-reported worry about COVID-19. Conclusion: During the first year of the COVID-19 pandemic, geographic differences in service and policy contexts likely influenced avoidance of health and harm reduction services by people who use drugs in the United States and Canada more than individual differences between people. Highlights: People who use drugs avoided treatment, harm reduction during COVID-19. There were large differences between U.S. and Canadian cities in avoidance. The only factor associated with avoiding syringe service was worry about COVID-19.